2022
DOI: 10.1111/gcb.16319
|View full text |Cite
|
Sign up to set email alerts
|

Body mass and cell size shape the tolerance of fishes to low oxygen in a temperature‐dependent manner

Abstract: Aerobic metabolism generates 15-20 times more energy (ATP) than anaerobic metabolism, which is crucial in maintaining energy budgets in animals, fueling metabolism, activity, growth and reproduction. For ectothermic water-breathers such as fishes, low dissolved oxygen may limit oxygen uptake and hence aerobic metabolism. Here, we assess, within a phylogenetic context, how abiotic and biotic drivers explain the variation in hypoxia tolerance observed in fishes. To do so, we assembled a database of hypoxia toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 91 publications
0
21
1
Order By: Relevance
“…The current results present several opportunities for future research on HIFA in fishes. For example, tolerance to hypoxia measured at the organismal level demonstrates a strong phylogenetic signal among ray-finned fishes 72 , and future research could assess whether hypoxia-tolerant lineages are associated with the specific amino acid variants in HIFα subunits reported here. Furthermore, in fishes as in other vertebrates, HIF1A has received considerably more attention than the other HIFA paralogs.…”
Section: Discussionmentioning
confidence: 92%
“…The current results present several opportunities for future research on HIFA in fishes. For example, tolerance to hypoxia measured at the organismal level demonstrates a strong phylogenetic signal among ray-finned fishes 72 , and future research could assess whether hypoxia-tolerant lineages are associated with the specific amino acid variants in HIFα subunits reported here. Furthermore, in fishes as in other vertebrates, HIF1A has received considerably more attention than the other HIFA paralogs.…”
Section: Discussionmentioning
confidence: 92%
“…However, while small cells have a better capacity for oxygen uptake, the higher energetic costs to maintain their electrochemical gradients are a disadvantage as more energy is required to maintain the electrochemical gradients across cellular membranes (Czarnołęski et al, 2013(Czarnołęski et al, , 2015(Czarnołęski et al, , 2018Gupta et al, 1978;Kozłowski et al, 2003;Szarski, 1970Szarski, , 1983. Therefore, cell size reflects a balance between the energetic costs and the benefits for oxygen diffusion and the optimal cell size is therefore likely to be temperature dependent (Hermaniuk et al, 2021;Verberk et al, 2022;Walczyńska et al, 2015). We observed that cell size category (small, medium and Normoxia (21 kPa) large) across our six isolines modulated the effects of temperature and oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for oxygen constraints related to heat stress is stronger for aquatic ectotherms than for terrestrial ectotherms (Leiva et al, 2019;Verberk et al, 2016), likely because of the difficulties involved: water holds less oxygen, impedes oxygen diffusion and because of the higher density and viscosity of water compared to air, it takes more energy to move water across respiratory organs such as gills (Dejours, 1981;Schmidt-Nielsen, 1997). There is also evidence that whether larger animals are more prone to oxygen limitation differs between air and water breathers (Harrison et al, 2018;Verberk et al, 2022). In air breathers, larger organisms rely to a larger extent on air convection for oxygen transport, rather than air diffusion, making them less prone to oxygen limitation (Greenlee et al, 2007).…”
mentioning
confidence: 99%
“…There is also direct evidence that changes in cell size are a component of plasticityand evolutionary-related changes in adult size [7,19,21,[25][26][27][28]. Undoubtedly, the number and size of the cells that make up an organism have consequences for organismal performance [29][30][31][32][33], but it is unclear whether the cellular structure of tissues is systemically organized throughout the metazoan body or whether it is arranged locally to suit tissue-specific functions. A clear answer to this fundamental question is unavailable largely because previous studies have rarely focused on cell-size variance among organisms and even then have tended to target single cell types [10,21,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%